Patient lumbar discectomy journey (DiscJourn) in the UK: a qualitative study - Alison B Rushton; Nicola R Heneghan; Louise White; Navin Furtado; Annabel Masson; Karl Baraks; Zeeshan Parvez (BMJ Open)
Objectives To gain insight into patients’ views, perceptions, experiences and expectations postlumbar discectomy.Methods A qualitative study using interpretative phenomenological analysis (IPA) purposively recruited patients undergoing lumbar discectomy at one UK spinal centre. Purposive criteria included age, sex, ethnicity, symptom duration, work/sick leave, education level and co-existing psychological issues. Semi-structured interviews were conducted using a patient co-constructed topic guide. Interview transcriptions were analysed in accordance with IPA. Strategies enhancing trustworthiness included suspension of judgements and presuppositions, reflexivity, iterative coding process and critique from co-investigators.Results Data from 14 participants (eight elective, 6 emergency surgery) informed four themes. The theme ready to move forwards was characterised by high satisfaction with post-operative improvement, positivity and optimism, with readiness to work towards personal goals. The theme post-operative fear and uncertainty was characterised by reflections on pre-operative difficulties fuelling fear about potential recurrence and long-term impacts. The theme of advice and guidance considered important was characterised by the expectation and value of support provided (verbal, written); instances of negative influences from healthcare interactions and access to unregulated patient information sources suggest scope for future improvement. The final theme, heterogeneity in peri-operative needs, was characterised by variation in depth/access to patient information, perceived post-operative support and wide-ranging preoperative activity/fitness.Conclusions Surgery offers physical and psychosocial changes which could be better harnessed to positively influence recovery through high quality verbal/written communication. Peri-operative advice and guidance was valued; while this was sufficient for some, personalised rehabilitation should be available owing to the identified heterogeneity.